Bone changes in infants with congenital syphilis - Silva, Sandra F Moreira; Prebianchi, Patricia A.; Dias, Carolina F.; Akel Júnior, Akel N.; Dalvi, Ludmila G.; Frauches, Diana O. (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: syphilis morbidity in intra-uterine life, produces negative outcomes in more than 50% of cases and complications in live births. Bone injuries are frequent in congenital syphilis (CS), occurring in 70 to 100% of the cases. Objective: to report cases of ten infants diagnosed with early SC and bone changes to the radiological examination of long bones, accompanied in the infectology service of HINSG. Case report: ten infants had bone injuries among children hospitalized with CS in HINSG, six female and four male. Half of the metropolitan region of Vitória, two from the interior and three from state of Bahia. Two were less than a month old. Six of the mothers had prenatal care, three were diagnosed with syphilis during pregnancy and only one was properly treated. Two children had osteomyelitis, and with a lytic lesion in the tibia and the other had periostitis. More than one bone was affected in six infants. Bones most affected: tibia (7/10), femur (6/10), humerus (5/10), radio (2/10) and ulna (2/10). Common symptom among all were frequent crying with movement of members. Reason why mothers have sought medical service. Discussion: changes are important in radiological diagnosis of CS. In this study 60% of mothers have prenatal care, one was treated correctly and none of the children were diagnosed and treated soon after birth, only receiving proper medication after diagnosis in our service. Radiological changes of CS may happen after installation according to time of infection. Various injuries may occur, including injuries of CS early: osteomyelitis diaphyseal, osteítes and periostitis. Osteochondritis affects cartilage in areas of growth. Injury of late CS are severe, can cause physical deformities and pathological fracture in children, necrosis of bone and osteolysis in adults and sometimes linking up with pyogenic infection or spread to adjacent tissues, with formation of fistulas skin painless.